Réponses

2014-02-06T18:19:03+01:00
Bonsoir

a = 2x
b = x²
c = 5x
d = 6x²
e = 6x
f = 2x +3
g = 2x² +3x
h = 3x² -x +5
i = 7x -7
j = -5x

a = 6x -10
b = 35 -10x
c = -4 +20x
d = 10x - 6x²
c'est très gentil de ta part merci !! bonne soirée
2014-02-06T18:37:44+01:00
1) Dans le 1 les résultats sont mis directement

A= 2x
B= x²
C= 5x
D= 6x²
E =6x
F = 2x + 3
G = 2x² + 3x
H = 3x² - x + 5
I = 7x - 4
J = - 5x

2)

A = 2 ( 3x -5 ) = 6x -10
B = 5 (7 - 2x ) = 35 - 10x
C = - 4 ( 1- 5x) =  - 4 + 20x
D = 2x ( 5 - 3x ) = 10x - 6x²